Computational investigation to explore the effects of metals (Mg, Ca, Sr) doping on phase transition, electronic band structure and their repercussions on optical, elastic and mechanical properties of BaThO3. (1st January 2023) - Gillani, S S A; Awais, M; Atif, M; Zeba, I; Shakil, M; Ahmad, Riaz
Abstract: The effect of metals (Mg, Ca, Sr) doping concentration on phase transition, electronic band structure, and their repercussions on the optical, elastic, and mechanical properties of BaThO3 is presented. At 1.40% doping of Mg, Ca, and Sr-atom, the structure of BaThO3 remains cubic. However, it changes from cubic to a pseudo-cubic tetragonal phase at doping concentrations of 4.22% and 7.04%. A systematic substantial shrinking of the band gap is observed in all cases of doping, and its nature remains direct on the G-symmetry point. The reduction in the band gap is explained by the total density of states (TDOS), partial density of states (PDOS), and elemental partial density of states (EPDOS) in the line of phase transformation. The optical response of a doped compound shows a red shift in the absorption edge, whereas the refractive index increases from 2.067–2.227 with Mg-doping and slightly decreases with Ca and Sr doping. For cubic and tetragonal symmetry, the computed elastic constants follow the mechanical stability criteria for each doping concentration, except at 7.04%Ca doping. Furthermore, the bulk modulus ( B ), shear modulus ( G ), Young's modulus ( E ), Poisson's ratio, and anisotropic factor ( A ) are estimated by utilizing elastic parameters. The B / G value is also determined to assess the ductile/brittle character of pure and doped compounds. Moreover, at 4.22%Ca, 7.04%Ca, and 4.22%Mg doping, non- homogeneity is observed due to negative stiffness and very high values of Poisson's ratio. The modification in structural, electronic, optical, elastic, and mechanical properties with Ca, Mg, and Sr-doping would make them an appropriate candidate for better optimization in UV filters due to the existence of their absorption spectra in the UV region.